Design and fabrication of active noise control system for a grass cutter. (April 2021) - Khan, Rahmatullah; Muzammil, Mohammad; Farooq, Omar
Active noise control technique was used to reduce noise generated by a grass cutting machine. Grass cutting machine running on a diesel engine generates loud noise of about 105 dBA. Based on the spectral analysis of engine noise, it was observed that frequencies in the range of 440–5000 Hz were having more noise power. An active noise control circuit was designed and fabricated using operational amplifiers. The active noise control circuit was tested with the help of a duct made of thermocol. Results show that reduction in noise up to 10 dBA was obtained when the active noise control circuit was used with a duct made of thermocol, while a reduction up to 5 dBA was obtained when used on a grass cutting machine. The active noise control system developed may be used to reduce noise generated by a grass cutting machine.